The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/2014gl061679
|View full text |Cite
|
Sign up to set email alerts
|

First observation of the anomalous electric field in the topside ionosphere by ionospheric modification over EISCAT

Abstract: We have developed an active ground-based technique to estimate the steady state field-aligned anomalous electric field (E*) in the topside ionosphere, up to~600 km, using the European Incoherent Scatter (EISCAT) ionospheric modification facility and UHF incoherent scatter radar. When pumping the ionosphere with high-power high-frequency radio waves, the F region electron temperature is significantly raised, increasing the plasma pressure gradient in the topside ionosphere, resulting in ion upflow along the mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…In our experiment, the F region electron temperature is raised up to 3,000 K, and the current density reaches 0.02 μA/m 2 . This value is smaller but of the same order as the downward current density observed by Kosch et al () (0.06 μA/m 2 ) during the ionospheric modification experiments performed in the auroral latitudes. Kosch et al () suggested the mechanism for anomalous resistivity due to low‐frequency ion acoustic waves generated by the pump‐induced flux of suprathermal electrons, which are produced near the pump wave reflection altitude by plasma resonance and also result in artificially induced optical emissions.…”
Section: Interpretation Of the Observational Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…In our experiment, the F region electron temperature is raised up to 3,000 K, and the current density reaches 0.02 μA/m 2 . This value is smaller but of the same order as the downward current density observed by Kosch et al () (0.06 μA/m 2 ) during the ionospheric modification experiments performed in the auroral latitudes. Kosch et al () suggested the mechanism for anomalous resistivity due to low‐frequency ion acoustic waves generated by the pump‐induced flux of suprathermal electrons, which are produced near the pump wave reflection altitude by plasma resonance and also result in artificially induced optical emissions.…”
Section: Interpretation Of the Observational Resultssupporting
confidence: 62%
“…This value is smaller but of the same order as the downward current density observed by Kosch et al () (0.06 μA/m 2 ) during the ionospheric modification experiments performed in the auroral latitudes. Kosch et al () suggested the mechanism for anomalous resistivity due to low‐frequency ion acoustic waves generated by the pump‐induced flux of suprathermal electrons, which are produced near the pump wave reflection altitude by plasma resonance and also result in artificially induced optical emissions. During the SURA heating experiment reported here, the SWARM satellite discovers a more complex signature, implying generation of eddy electric currents, which are likely associated with another physical mechanism, namely, unipolar diffusion with the formation of eddy currents.…”
Section: Interpretation Of the Observational Resultssupporting
confidence: 62%
“…The procedure for obtaining the spectra is the same as described by 249 Blagoveshchenskaya et al (2014). possible to make such a comparison between two heater pulses of different durations obtained 255 from two different experiments under different background conditions.…”
Section: Experiments On 28 October 2013 216mentioning
confidence: 99%
“…However, the SAMI2 simulations with moderate peak heating rates up to 5000 K/s do not explain the fast appearance of artificial ducts and O + ion outflows in the topside ionosphere. Kosch et al [2010;2014b] have shown that in order to match the observations of the HFinduced ion outflows from the EISCAT UHF ISR, a 1-2 µV/m downward electric field is needed in addition to the electron pressure gradient. The latter, however, does not explain the fast timescale as the average upward speed does not exceed ~0.5 km/s.…”
Section: Numerical Modeling Of Artificial Ductsmentioning
confidence: 99%